Taxonomy and biogeography of bivalves of the genus Cuspidaria from southern Southwestern Atlantic deep sea - Pacheco, Leonel Ivan; Teso, Silvia Valeria; Pastorino, Roberto Santiago Guido (Malacologia)
In this paper, a taxonomic review of the bivalves of the genus Cuspidaria Nardo, 1840 from the southern southwestern Atlantic is conducted. Specimens deposited in malacological collections and samples collected onboard the R/V Puerto Deseado off Mar del Plata (~36°S) and MPA Namuncurá/Burdwood Bank area (~54°S), between 200 and 3,000 m depth, are the focus of this revision. The specimens were analyzed through conchological and anatomical features. The geographic and bathymetric distributions for each species are provided and possible factors determining biogeographic patterns are discussed. As a result, Cuspidaria infirma n. sp., Cuspidaria cancellata n. sp., Cuspidaria namuncura n. sp., and Cuspidaria cf. kerguelensis (Smith, 1885), are described. In addition, Cuspidaria exigua (Jeffreys, 1876), Cuspidaria bicarinata Jeffreys, 1882, Cuspidaria platensis (Smith, 1885), Cuspidaria tenella Smith, 1907, Cuspidaria infelix Thiele, 1912, and Cuspidaria barnardi Knudsen, 1970 are redescribed after the study of new specimens. Elliptic Fourier analyses were performed for each side of the shell to delimit species objectively using their shape. Results showed a clear differentiation on both valves among species. Cuspidaria bicarinata and Cuspidaria exigua, both North Atlantic species, were recorded for the first time in the southwestern Atlantic, and Cuspidaria infelix and Cuspidaria tenella, both Antarctic/sub-Antarctic species, expanded their distribution northwards. Two cluster analyses, for species and areas respectively, revealed a vertical zonation, separating species into two different groups highly corresponding to deep-sea water mass distributions. Fil: Pacheco, Leonel Ivan. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Teso, Silvia Valeria. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo ...